2019
DOI: 10.1097/rhu.0000000000001131
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Rheumatic Diseases and Quality of Life in the Saraguro Indigenous People, Ecuador

Abstract: Rheumatic diseases are more prevalent and aggressive in indigenous population groups, providing medical attention for which poses a challenge for the rheumatologist. Objective To estimate the prevalence of musculoskeletal (MSK) disorders and rheumatic diseases in the Saraguro indigenous people in Ecuador, as well as to identify the main factors associated with the health status of this population. Methods This observational, cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…2019 [99] Spain 707 207 62; ≥40 NA 398 Doctor-diagnosed OA 2019 Cross-sectional Random sampling Abstract Guevara SV et al. 2019 [100] Ecuador 2,687 177 44 (20); ≥18 NA 1,690 ACR 2016–2018 Cross-sectional Random and mixed (stratified and conglomerate) Full text Hvidberg MF et al. 2019 [14] Denmark 4,555,439 177,662 ≥16 NA 2,314,163 ICD-10 codes 2013 Longitudinal NA Full text Hong JW et al.…”
Section: Resultsmentioning
confidence: 99%
“…2019 [99] Spain 707 207 62; ≥40 NA 398 Doctor-diagnosed OA 2019 Cross-sectional Random sampling Abstract Guevara SV et al. 2019 [100] Ecuador 2,687 177 44 (20); ≥18 NA 1,690 ACR 2016–2018 Cross-sectional Random and mixed (stratified and conglomerate) Full text Hvidberg MF et al. 2019 [14] Denmark 4,555,439 177,662 ≥16 NA 2,314,163 ICD-10 codes 2013 Longitudinal NA Full text Hong JW et al.…”
Section: Resultsmentioning
confidence: 99%
“…1). Of these, 13 publications reported studies of populations from the Latin American region [10][11][12][13][14][15][16][17][18][19][20][21][22], with over 60% of studies from Mexico [11,[16][17][18]22] and Ecuador [13][14][15] (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…2). All of the 13 studies [10][11][12][13][14][15][16][17][18][19][20][21][22] reported knee OA and 5 (38%) studies The overall prevalence of physician-diagnosed symptomatic knee OA among men and women ≥ 18 years of age (Table 2) ranged from 1.55% in the Peruvian population [21] to 7.4% in Ecuador [14]. Among those ≥ 40 years of age in Mexico, the total prevalence of symptomatic knee OA was 19.6% [18].…”
Section: Resultsmentioning
confidence: 99%
“…In Ecuador, the study on the quality of life in older adults has begun, but in an incipient way [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Bustamante et al [ 49 ] measured quality of life as a one-dimensional construct and found that a greater sense of quality of life is associated with job type and educational level.…”
Section: Introductionmentioning
confidence: 99%
“…For their part, Gordillo Altamirano et al [ 50 ] determined that physical functionality is associated with a greater perception of quality of life in terms of physical health, while factors such as anxiety and depression negatively affect the quality of life of older adults, specifically their mental health. Guevara et al [ 56 ] concluded that the prevalence of rheumatic diseases influences a lower quality of life in indigenous older adults. In this sense, the present study differs from others carried out in the elderly population of Ecuador since it considers the multidimensionality of the quality of life and incorporates numerous sociodemographic factors that have not been analyzed in this population (e.g., sports practice, the performance of medical examinations).…”
Section: Introductionmentioning
confidence: 99%